Sanitizantes tradicionais vs naturais: desafio in vitro e in situ em bactérias multirresistentes - Ferreira, Gabriella Rayane Aparecida (2024)
The variety of pathogenic microorganisms, along with the diversity of virulence factors, resistance, adaptation, and various forms of transmission, makes the development of effective control strategies and hygiene practices increasingly challenging in industrial and hospital environments. The dissertation is divided into two chapters: the first is a literature review on the subject, and the second is a scientific article which aims to evaluate the efficiency of ten biocidal agents, including traditional and natural ones, against eleven bacteria, eight of which are multidrug-resistant (MR) from hospital environments and the food industry. To achieve this objective, we determined the Minimum Bactericidal Concentration (MBC), which established the concentrations and times required to inhibit the growth of bacterial strains. Next, the efficiency test was performed, specific to the acceptance of new chemical agents, and the in-situ test conducted in a hospital environment to verify the antimicrobial effect in routine cleaning. The products tested included those traditionally used and natural ones - Peracetic Acid, two types of ammonium quaternaries, Biguanide, Chlorhexidine Digluconate, Pine Oil, Neem Extract, Melaleuca Oil, Orange Oil and Lactic Acid. Preliminary tests (MBC) showed that five strains resisted to 50% of the agents tested, and Pseudomonas aeruginosa resisted 7/10 chemical agents. Peracetic acid, chlorhexidine digluconate and neem extract inhibited all the strains by MBC. After defining the target concentrations, we identified efficiency for all the traditional agents, with an average reduction of 7.07 ± 0.33 log, and for the extract (average of 6.60 ± 0.33 log) in controlling the 11 strains. The application of the in-situ test led to the conclusion that peracetic acid had the best effect, since there was no bacterial growth. However, the reduction of over 99.99% after using biguanide, neem extract, tea tree oil and orange oil highlights the possibility of using natural alternatives for bacterial control on surfaces.